The Urgency of Public Policy in Combating Deepfake Pornography: A Comparative Analysis of Indonesia, South Korea, Colombia - Niken Yoan Tanjung (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The rapid advancement of generative artificial intelligence (AI) presents a grave threat through the proliferation of deepfake pornography, known as non-consensual synthetic intimate imagery (NSII). Indonesia's current positive legal framework (EIT Law, Pornography Law, TPKS Law, PDP Law, and the new Criminal Code) remains generic and unequipped to address the unique characteristics of AI-based biometric identity manipulation. This normative legal research aims to diagnose the weaknesses in Indonesian law and formulate a responsive policy design using statutory, conceptual, and comparative approaches. Analyzing secondary legal materials through Lawrence M. Friedman’s tripartite legal system model and John W. Kingdon’s policy window theory, this study compares the dynamics of legal reform in Indonesia, South Korea, and Colombia. The findings reveal a comprehensive legal vacuum in Indonesia across three dimensions: the absence of explicit criminal norms (substance), the lack of specialized institutional units with rapid takedown and digital forensic capabilities (structure), and the failure to transform viral cases into organized public advocacy (legal culture). Comparative analysis demonstrates that South Korea's swift legal reform succeeded due to the convergence of problem, policy, and political streams fostered by policy entrepreneurs, whereas Colombia suffered regulatory stagnation due to immature policy streams despite strong public outcry. Consequently, Indonesia is advised to adopt the functional equivalence principle by criminalizing the creation of NSII content on the substantive level, establish rapid-action units and digital forensic standards structurally, and consolidate civil society advocacy to effectively leverage the policy window culturally.